Navigating communication challenges in the post-pandemic era: perspectives from teachers in a Philippine higher education institution - Baltazar, Jasmyn; Caples, Trixie Jayne; Isio, Adriel Kieth; Sitoy, Ranilyn; Nacionales, Joseph; Claridad, Norberto (Journal of Language, Literature, Social and Cultural Studies, 2023)
The COVID-19 pandemic has presented an opportunity for the education sector, particularly in higher education, to reconsider how they adapt to the post pandemic era. However, several challenges emerge, particularly regarding the communication between teachers and students. This study was undertaken to find out how teachers communicate with students and the communication challenges that they encountered in the post-pandemic period. A qualitative research approach was applied throughout the study, specifically the utilization of the Interpretative Phenomenological Analysis (IPA) method. The data gathered from nineteen (19) teachers was analyzed through thematic analysis. The coding cycle used was vivo coding, followed by eclectic coding and axial coding for refining codes. Responses revealed five specific challenges that was faced by the teachers: (1) pandemic impact on students’ attitudes and learning (2) language and communication barriers, (3) technological challenges in education, (4) lack of infrastructures building gaps in classroom environment, and (5) teachers’ preparedness and effectiveness. It is significant that teachers know how to apply different strategies in order to counter communication challenges that they may face. Few recommendations to improve the findings of the study are discussed at the end of this paper.